If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+30=-4(8x-9)
We move all terms to the left:
6+30-(-4(8x-9))=0
We add all the numbers together, and all the variables
-(-4(8x-9))+36=0
We calculate terms in parentheses: -(-4(8x-9)), so:We get rid of parentheses
-4(8x-9)
We multiply parentheses
-32x+36
Back to the equation:
-(-32x+36)
32x-36+36=0
We add all the numbers together, and all the variables
32x=0
x=0/32
x=0
| 2/15=3=2x | | 2x/3x-15=8/3 | | 3(4x+9)=-30+33 | | L3/5g-1/3=-10/3 | | -11s+3s+6s=-6 | | 1-1/x=2/x^2 | | s4-19=93 | | 10p+p-4p=14 | | -9x^2-8x-1=0 | | 9(4b-1)=2(9b+4) | | T-(5t+3)=19 | | 5(3x+9)=-46+1 | | E^x-2=0 | | 2(p-4)-4(p-3)=6 | | 12x+36=10-6x | | 10.88x=54.40 | | (2x+4)^2-(2x+2)^2-(2x)^2=0 | | 7h+29=27 | | −4x2−7=−11 | | 4x-(23)=3x+7-2x | | 3x+25=6x+28 | | 8(2x+3x=2)=-4x+124 | | −4x^2−7=−11 | | 60x-1000=-25x+2400 | | 2|5x-1|+3=14 | | t÷4-6=13 | | 5x5=140 | | −4x^2−7=−11 | | -6+-20=9+h | | 7.25(40)=10.88x=344.40 | | -4=-12+14x | | x³+18x²+33x=0 |